GEOLOCATION USAHA SYARIAH KOTA MEDAN - Nurliadi Nurliadi (LPPM Politeknik LP3I Medan, 2018)
Medan city is one of the largest cities in Indonesia which has a variety of tourist objects and is also known as a culinary paradise that can be used as a culinary tourist destination for people in Indonesia. But the absence of a forum that provides information about businesses whose products have a halal label makes Muslim communities very careful in using or consuming the products they buy. As for the development stage for data collection in building a geographic information system (GIS) website, the Medan city sharia business used field research methods and literature studies aimed at gathering all information about sharia business data. This geographic information system aims to be able to provide information about the location of sharia businesses that are equipped with geolocatian that provide the route that will be passed directly to the location of the sharia business to be addressed. This information system can be utilized to help the community in knowing information about the locations of all sharia businesses in the city of Medan. This information system can also be used by sharia business actors to register their sharia businesses as well as a promotional event to introduce products and goods to the public at large through the Medan sharia business geographic information system. The results obtained from this website are that it can display all sharia businesses in the city of Medan, equipped with geolaction to display the route to the intended business and businesses can register their businesses so that the public can find out and hopefully this website can gradually overcome the problem to help people find sharia businesses in the city of Medan